Don't look down: the consequences of job loss in a flexible labour market - Upward, Richard; Wright, Peter (Wiley, 2017)
We estimate the earnings, hours and income effects of job loss for a representative sample of UK workers from 1991–2007. We follow workers before and after job loss, regardless of their labour market state, and we match displaced workers with similar non-displaced workers. This provides a more comprehensive picture of the effect of job loss in the UK than previously available. Job loss causes a long-run reduction in income which is mainly due to reductions in monthly pay rather than in employment propensity. Income from other labour market states and from welfare payments does little to compensate for income losses. This lack of a “safety net” means that job loss in the UK has a similar impact to job loss in the US.